Neuregulin 1 improves cognitive deficits and neuropathology in an Alzheimer’s disease model - Jiqing Xu; Fred de Winter; Catherine Farrokhi; Edward Rockenstein; Michael Mante; Anthony Adame; Jonathan Cook; Xin Jin; Eliezer Masliah; Kuo-Fen Lee (Scientific Reports)
Abstract Several lines of evidence suggest that neuregulin 1 (NRG1) signaling may influence cognitive function and neuropathology in Alzheimer’s disease (AD). To test this possibility, full-length type I or type III NRG1 was overexpressed via lentiviral vectors in the hippocampus of line 41 AD mouse. Both type I and type III NRG1 improves deficits in the Morris water-maze behavioral task. Neuropathology was also significantly ameliorated. Decreased expression of the neuronal marker MAP2 and synaptic markers PSD95 and synaptophysin in AD mice was significantly reversed. Levels of Aβ peptides and plaques were markedly reduced. Furthermore, we showed that soluble ectodomains of both type I and type III NRG1 significantly increased expression of Aβ-degrading enzyme neprilysin (NEP) in primary neuronal cultures. Consistent with this finding, immunoreactivity of NEP was increased in the hippocampus of AD mice. These results suggest that NRG1 provides beneficial effects in candidate neuropathologic substrates of AD and, therefore, is a potential target for the treatment of AD.